Pelvic Tuberculosis Simulating an Ovarian Tumor at a Stage of Peritoneal Carcinosis - Mbodj, Mohameth; Ba, Idrissa D.; Dieng, Yaay Dior K. B. (Scientific Research Publishing, 2021)
Tuberculosis is a global public health problem with 10 million people devel oping an active form each year. The exact incidence of the pelvic form of tu berculosis is not known due to under-reporting of asymptomatic cases, vague symptomatology and lack of reliable diagnosis. We report a case of ovarian tuberculosis mimicking cancer and peritoneal carcinosis. The case involved a 15-year-old girl, hospitalized for severe pelvic pain and secondary amenorr hea. The examination showed an altered general state, a fever, a sensitive dis tended abdomen. The biology showed an elevation of Ca125 to 357 IU/ml. The CT scan showed a latero-uterine mass taking contrast in a heterogeneous way with an irregular and nodular thickening of the peritoneum making evoke a peritoneal carcinosis. Exploratory laparotomy found a bilateral ovarian mass with ileo-ileal, ileo-parietal and ileo-ovarian adhesions. Biopsy of the mass and the peritoneum showed a caseo-follicular gigantocellular epitheloid granulomatosis.
Keywords: Tuberculosis; Granulomatosis; Carcinosis; Ca125; Université Cheikh Anta Diop; CEA-SAMEF; Fatim Tall; Amadou Sow